2014
DOI: 10.1111/tan.12440
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protein tyrosine phosphatase gene (PTPN22) polymorphisms on rheumatic heart disease susceptibility in North Indian population

Abstract: This study was aimed to assess the association of Protein tyrosine phosphatase non-receptor22 (PTPN22) gene single nucleotide polymorphisms (SNPs) with rheumatic heart disease (RHD) susceptibility in 400 RHD patients and 300 controls. The PTPN22 polymorphisms (rs2476601, rs1217406 and rs3789609) were genotyped using Taqman probes (Applied Biosystems, Foster City, CA). Statistical analysis was performed by spss and haplotype analysis by snpstat. The frequencies of variant alleles were not different between cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The pooled concordance risk for ARF was 44% in monozygotic twins and 12% in dizygotic twins (OR 6.39, p<0.001), with an estimated heritability of 60%. To date, targeted genomic investigations have examined select genes involved in immune regulation including human leukocyte antigens (HLA), transforming growth factor-beta1, toll-like receptor 5, angiotensin I-converting enzyme gene, PTPN22, and signal transducers and activators of transcription (STATs) gene polymorphisms [ 17 23 ]. The most robust data comes from studies of the major histocompatibility complex human leukocyte antigens [ 3 , 24 ], with many finding polymorphisms within the HLA-DR locus, including a study from Uganda [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pooled concordance risk for ARF was 44% in monozygotic twins and 12% in dizygotic twins (OR 6.39, p<0.001), with an estimated heritability of 60%. To date, targeted genomic investigations have examined select genes involved in immune regulation including human leukocyte antigens (HLA), transforming growth factor-beta1, toll-like receptor 5, angiotensin I-converting enzyme gene, PTPN22, and signal transducers and activators of transcription (STATs) gene polymorphisms [ 17 23 ]. The most robust data comes from studies of the major histocompatibility complex human leukocyte antigens [ 3 , 24 ], with many finding polymorphisms within the HLA-DR locus, including a study from Uganda [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the South Asian analysis, genetic material was obtained with informed consent from cases and controls recruited to two distinct studies. Specifically, we expanded an existing collection in Northern India [12][13][14][15][16], and we used samples from our existing collection of Pacific Islanders [8], specifically the Fijians of Indian descent. Cases of RHD were defined on the basis of: a history of valve surgery for RHD, a definite RHD diagnosis by echocardiography, or borderline RHD diagnosis by echocardiography with prior acute rheumatic fever [17].…”
Section: Sample Collectionsmentioning
confidence: 99%
“…In India, adults with incident or prevalent RHD were recruited as cases from a single large referral hospital, the Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, Uttar Pradesh; recruitment was limited to patients with an echocardiographic diagnosis of RHD [17]. Controls were recruited based on normal echocardiograms and the absence of prior family history of rheumatic fever [12][13][14][15][16]. In total, DNA samples were obtained from 543 cases and 397 controls.…”
Section: Sample Collectionsmentioning
confidence: 99%
“…Single-nucleotide polymorphisms in a number of genes were found in patients with RHD compared to controls, namely protein tyrosine phosphatase non-receptor 22 (PTPN22), 41 signal transducers and activators of transcription (STAT), 42 angiotensin converting enzyme (ACE I/D), 43 TNF-α, 44 , 45 transforming growth factor (TGF-β1), 46 , 47 and TLR5 48 (Table 2) . Studies in North Indians with RHD suggest that the (PTPN22) haplotype, which encodes an important negative regulator of T-cell activation, modulates the risk of developing RHD.…”
Section: The Role Of Genetic Studiesmentioning
confidence: 99%
“…Studies in North Indians with RHD suggest that the (PTPN22) haplotype, which encodes an important negative regulator of T-cell activation, modulates the risk of developing RHD. 41 In a Turkish population, however, it was demonstrated that the PTPN22 R620W polymorphism was not associated with RHD, 49 showing that genetic differences exist among populations from different regions of the world, therefore making it relevant to implement similar studies in Africa.…”
Section: The Role Of Genetic Studiesmentioning
confidence: 99%